PENGARUH PAJAK KENDARAAN BERMOTOR DI SAMSAT KOTA MADIUN TERHADAP PENDAPATAN ASLI DAERAH - Fanida, Eva Hany; Fitrie, Revienda Anita; Maruf, Muhammad Farid; Yustanika, Nuarsada; Shafira, Katerina; Abdillah, Dicky Candra; Asa Handsant, Farah Fatima; Dwi Iswahyudi, Sultan Ahmad (Jurnal Daya Saing, 2025)
This study examines the impact of Motor Vehicle Tax (PKB) on the Regional Original Revenue (PAD) of Madiun City using a qualitative descriptive approach. The findings indicate that PKB contributes significantly to the PAD of Madiun City, with percentages of 41.89% (2022), 45% (2023), and 45.21% (2024), categorized as “Good.” Factors influencing tax compliance include tax knowledge, payment location distance, and the amount of administrative sanctions. Despite the number of motor vehicles, the contribution of PKB to PAD remains consistent. The distribution of PKB revenue is allocated at 60% for the Madiun City Government and 40% for the East Java Provincial Government. Efforts to increase taxpayer awareness and digital-based payment service innovations are recommended as strategic measures to optimize PKB revenue as a sustainable source of regional income. Keywords: Motor Vehicle Tax, Regional Original Revenue, Taxpayer Compliance, Tax Contribution, SAMSAT Madiun City.